The first record of Mexiconnus Jałoszyński in Costa Rica with description of a new species (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2022)
To date, Mexiconnus Jałoszyński was a monotypic genus known to occur in Chiapas, Mexico. The sole species, M. mexicanus (Franz), was unique among Stenichnini in having strongly broadened protarsi with a conspicuous setal cushion on the ventral side of the protarsomere 1. A new species, M. triops sp. n., is described, based on a male collected in central Costa Rica. In contrast to the type species of the genus, the male of M. triops is wingless, microphthalmous and depigmented, a set of features that suggest a possible endogean life habit.